Electronically Tunable Universal Biquad Using a Single Active Component - Sagbas, Mehmet; Ayten, Umut E.; Koksal, Muhammet; Herencsar, Norbert (IEEE, 2015)
In this work, a novel voltage-mode (VM) single input four-output universal filter topology is presented. The proposed structure uses two resistors, two capacitors and only one voltage differencing current conveyor (VDCC) and generates all biquadratic filtering functions namely: low-pass (LP), hand-pass (BP), high-pass (HP) and hand-reject (BR). The quality factor and natural frequency of the filter can be adjusted electronically without changing the values of the passive components. Moreover, the circuit does not require any condition of component matching and has a good sensitivity performance with respect to tracking errors of passive components and the active parameter. PSpice simulation results confirm the results of the theoretical analysis.
Keywords: Voltage-mode circuits; biquadratic filters; universal filters; active filters; current conveyors; transconductance amplifiers; voltage differencing current conveyor; VDCC; VOLTAGE-MODE FILTER; HIGH-INPUT; BAND-PASS; DDCCS; OUTPUT; AMPLIFIERS; CONVEYORS; ELEMENTS; CDBA; Engineering; Telecommunications